Stable isotope evidence of plant water sources for alien and indigenous riparian trees in headwater streams, South Africa - Retang Anna Mokua; Paul Koeniger; Anthony Michael Swemmer; Rachel Keen; Mike Butler (Hydrological Sciences Journal, 2026)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

Allometric aboveground biomass equations to quantify carbon content of Southeast Australian saltmarsh vegetation - Jami Butler; Clare Duncan; Paul E. Carnell; Anirban Akhand; Stacey M. Trevathan-Tackett; Peter I. Macreadie (Regional Studies in Marine Science, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Effects of maternal contact and positive human contact during lactation on pork quality: Positive human contact to piglets during lactation improves pork loin muscle pH - Katelyn Tomas; Jemma Savaglia; Robert J.E. Hewitt; Kate J. Plush; Darryl N. D'Souza; Kym L. Butler; Paul H. Hemsworth; Alan J. Tilbrook (Meat Science, 2025)

Maternal contact and positive human interactions during lactation impact on pig stress resilience post-weaning - Katelyn Tomas; Jemma Savaglia; Kate J. Plush; Darryl N. D’Souza; Kym L. Butler; Paul H. Hemsworth; Alan J. Tilbrook (Applied Animal Behaviour Science, 2024)

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Development of subfamily-based consensus PCR assays for the detection of human and animal herpesviruses - God’spower Richard Okoh; Michelle Lockhart; Joanne Grimsey; David Whitmore; Ellen Ariel; Jeff Butler; Paul F. Horwood (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Consensus PCR assays that can be used to sensitively detect several herpesvirus (HV) species across the different subfamilies were developed in this study. Primers containing degenerate bases were designed to amplify regions of the DNA polymerase (DPOL) gene of alpha- and gamma-HVs, and the glycoprotein B (gB) gene of beta-HVs in a singleplex, non-nested touchdown PCR format. The singleplex touchdown consensus PCR (STC-PCR) was used to amplify the DNA of eight human and 24 animal HVs. The assay was able to detect the lowest DNA dilution of 10 −5 for alpha-HVs and 10 −3 for beta- and gamma-HVs. In comparison, lowest detection limits of 10 −5 , 10 −3 , and 10 −2 were obtained for alpha-, beta-, and gamma-HVs respectively when a nested PCR was used. The findings in this study suggest that the STC-PCR assays can be employed for the molecular surveys and clinical detection of novel and known HVs.

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Can element chemical impurities in aragonitic shells of marine bivalves serve as proxies for environmental variability? - Bernd R. Schöne; Soraya Marali; Anne Jantschke; Regina Mertz-Kraus; Paul G. Butler; Lukas Fröhlich (Chemical Geology, 2023)

Reply to Comment on Economic Contributions from Conserved Forests: Four Case Studies of the USDA Forest Service Forest Legacy Program - Helena Murray; Paul Catanzaro; Marla Markowski-Lindsay; Brett J Butler; Henry Eichman (Forest Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Economic Contributions from Conserved Forests: Four Case Studies of the USDA Forest Service Forest Legacy Program - Helena Murray; Paul Catanzaro; Marla Markowski-Lindsay; Brett J Butler; Henry Eichman (Forest Science, 2021)
Privately-owned forests provide important environmental, economic, and cultural benefits to the general public. Resulting impacts from landownership changes and conversion of working forests to other land uses threaten these benefits. The USDA Forest Service Forest Legacy Program (FLP) permanently protects threatened private forests that are of environmental, cultural, and economic importance to the greater public while keeping land ownership and forest management at the private or local level. FLP provides grants to state agencies to purchase conservation easements on private forestlands or, less frequently, acquisition by public agencies. We employed IMPLAN’s input-output model of the 2016 economy to estimate how land protected by FLP in four regions of the United States contributes to the economy. FLP land adds tens of millions of dollars of value annually and supports thousands of jobs in the four study areas and, due to the permanent protection of these lands, they will continue to do so in perpetuity. Nonfederal partners contributed 34%–60% of total project costs, highlighting the importance of land conservation to multiple stakeholders and the ability to leverage federal resources. The permanent nature of FLP protection provides long-term security for the economic and cultural benefits these lands provide.

An Optical Imaging System for Capturing Images in Low-Light Aquatic Habitats Using Only Ambient Light - Camille Pagniello; Jack Butler; Annie Rosen; Addison Sherwood; Paul Roberts; Edward Parnell; Jules Jaffe; Ana Širović (Oceanography, 2021)
It is preferable that methods for monitoring fish behavior, diversity, and abundance be noninvasive to avoid potential bias. Optical imaging facilitates the noninvasive monitoring of underwater environments and is best conducted without the use of artificial lighting. Here, we describe a custom-designed optical imaging system that utilizes a consumer-grade camera to capture images in situ in ambient light. This diver-deployed system can be used to collect time series of occurrences of animals while concurrently obtaining behavioral observations for two weeks to a month (depending on the sampling rate). It has also been configured to be paired with a passive acoustic system to record time-synchronized image and acoustic data. The system was deployed in a protected kelp forest off southern California and captured >1,500 high-quality images per day over 14 days. The images revealed numerous fish species exhibiting biologically important behaviors as well as daily patterns of presence/absence. The optical imaging system is a cost-effective tool that can be easily fabricated and improves upon many of the limitations of previous systems, including deployment length and image quality in low-light and limited-visibility conditions. The system provides a relatively noninvasive way to monitor shallow marine habitats, including protected areas, and can augment traditional survey methods by providing nearly continuous observations and thus yield increased statistical power.

Assessing the groundwater dependence of valley bottom wetlands in coal-mining environment using multiple environmental tracers, Mpumalanga, South Africa - Tebogo Madlala; Thokozani Kanyerere; Paul Oberholster; Mike Butler (Sustainable Water Resources Management, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Investigating Prolonged Neonatal Jaundice: A Staged Approach is Superior and Conducive to Breastfeeding - Jonathan Wayland Graham; Siba Prosad Paul; Sarah Mulholland; Steven Chi Tran; Charlotte Louise Butler; Rowan Douglas Mankiewitz; Georgia Beech (Indian Journal of Clinical Biochemistry, 2021)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Catalyzing sustainable fisheries management through behavior change interventions - Gavin McDonald; Molly Wilson; Diogo Veríssimo; Rebecca Twohey; Michaela Clemence; Dean Apistar; Stephen Box; Paul Butler; Fel Cesar Cadiz; Stuart J. Campbell; Courtney Cox; Micah Effron; et al. (Conservation Biology, 2020)
Small‐scale fisheries are an important livelihood and primary protein source for coastal communities in many of the poorest regions in the world, yet many are overfished and thus require effective and scalable management solutions. Positive ecological and socioeconomic responses to management typically lag behind immediate costs borne by fishers from fishing pressure reductions necessary for fisheries recovery. These short‐term costs challenge the long‐term success of these interventions. However, social marketing may increase perceptions of management benefits before ecological and socioeconomic benefits are fully realized, driving new social norms and ultimately long‐term sustainable behavior change. By conducting underwater visual surveys to quantify ecological conditions and by conducting household surveys with community members to quantify their perceptions of management support and socioeconomic conditions, we assessed the impact of a standardized small‐scale fisheries management intervention that was implemented across 41 sites in Brazil, Indonesia, and the Philippines. The intervention combines TURF reserves (community‐based territorial use rights for fishing coupled with no‐take marine reserves) with locally tailored social‐marketing behavior change campaigns. Leveraging data across 22 indicators and 4 survey types, along with data from 3 control sites, we found that ecological and socioeconomic impacts varied and that communities supported the intervention and were already changing their fishing practices. These results suggest that communities were developing new social norms and fishing more sustainably before long‐term ecological and socioeconomic benefits of fisheries management materialized.

A comparison of uterine contractile responsiveness to arginine vasopressin in oviparous and viviparous lizards - Jonathan W. Paul; Joshua O. Kemsley; Trent A. Butler; Jorge M. Tolosa; Michael B. Thompson; Roger Smith; Camilla M. Whittington (Journal of Comparative Physiology B, 2020)

Soy and tea intake on cervical cancer risk: the Singapore Chinese Health Study - Proma Paul; Woon-Puay Koh; Aizhen Jin; Angelika Michel; Tim Waterboer; Michael Pawlita; Renwei Wang; Jian-Min Yuan; Lesley M. Butler (Cancer Causes & Control, 2019)

Reconstruction of Atlantic herring ( Clupea harengus ) recruitment in the North Sea for the past 455 years based on the δ 13 C from annual shell increments of the ocean quahog ( Arctica islandica ) - Juan Estrella‐Martínez; Bernd R. Schöne; Ruth H. Thurstan; Elisa Capuzzo; James D. Scourse; Paul G. Butler (Fish and Fisheries, 2019)
Understanding the recruitment variability of the Atlantic herring North Sea stock remains a key objective of stock assessment and management. Although many efforts have been undertaken linking climatic and stock dynamic factors to herring recruitment, no major attempt has been made to estimate recruitment levels before the 20th century. Here, we present a novel annually resolved, absolutely dated herring recruitment reconstruction, derived from stable carbon isotope geochemistry (δ 13 C), from ocean quahog shells from the Fladen Ground (northern North Sea). Our age model is based on a growth increment chronology obtained from fourteen shells. Ten of these were micromilled at annual resolution for δ 13 C analysis. Our results indicate that the anthropogenically driven relative depletion of 13 C, the oceanic Suess effect ( oSE ), became evident in the northern North Sea in the 1850s. We calculated a regression line between the oSE ‐detrended δ 13 C results (δ 13 CṠ) and diatom abundance in the North Sea, the regression being mediated by the effect of phytoplankton on the δ 13 C of the ambient dissolved inorganic carbon. We used this regression to build an equation mediated by a nutritional link to reconstruct herring recruitment using δ 13 CṠ. The reconstruction suggests that there were five extended episodes of low‐recruitment levels before the 20th century. These results are supported by measured recruitment estimates and historical fish catch and export documentation. This work demonstrates that molluscan sclerochronological records can contribute to the investigation of ecological baselines and ecosystem functioning impacted by anthropogenic activity with implications for conservation and stock management.

Mesolithic human occupation and seasonality: sclerochronology, δ18O isotope geochemistry, and diagenesis verification by Raman and LA-ICP-MS analysis of Argyrosomus regius (meagre) sagittae otoliths from layer 1 of Cabeço da Amoreira Mesolithic shell midden (Muge, Portugal) - Rita Dias; Juan Estrella-Martínez; Paul Butler; Alexandra Nederbragt; Ian R. Hall; Pedro Barrulas; Anne France Maurer; Ana Mafalda Cardeira; José Mirão; Cleia Detry; Nuno Bicho (Archaeological and Anthropological Sciences, 2019)

Genetic mapping of a barley leaf rust resistance gene Rph26 introgressed from Hordeum bulbosum - Xiaohui Yu; Hoi Yee Kong; Vijitha Meiyalaghan; Seona Casonato; Soonie Chng; E. Eirian Jones; Ruth C. Butler; Richard Pickering; Paul A. Johnston (Theoretical and Applied Genetics, 2018)

Analytical performance of a platform for point-of-care CRP testing in adults consulting for lower respiratory tract infection in primary care - Veerle Matheeussen; Viviane Van Hoof; Katherine Loens; Christine Lammens; Anouk Vanderstraeten; Samuel Coenen; Chris C. Butler; Paul Little; Theo J. M. Verheij; Herman Goossens; Margareta Ieven (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

In Forest and Intact: Designating Future Use of Family-Forest-Owned Land - Marla Markowski-Lindsay; Paul Catanzaro; Kathleen Bell; David Kittredge; Ezra Markowitz; Jessica Leahy; Brett Butler; Anita Milman; Shorna Allred (Journal of Forestry, 2018)

3D Cell Culturing and Possibilities for Myometrial Tissue Engineering - Minoo Heidari Kani; Eng-Cheng Chan; Roger C. Young; Trent Butler; Roger Smith; Jonathan W. Paul (Annals of Biomedical Engineering, 2017)

The Application of Long-Lived Bivalve Sclerochronology in Environmental Baseline Monitoring - Juliane Steinhardt; Paul G. Butler; Michael L. Carroll; John Hartley (Frontiers in Marine Science, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Family Forest Owners’ Perceptions of Landowner Assistance Programs in the USA: A Qualitative Exploration of Program Impacts on Behaviour - Kyle Andrejczyk; Brett J. Butler; Brenton J. Dickinson; Jaketon H. Hewes; Marla Markowski-Lindsay; David B. Kittredge; Michael A. Kilgore; Stephanie A. Snyder; Paul F. Catanzaro (Small-scale Forestry, 2016)

A simple and inexpensive enteric-coated capsule for delivery of acid-labile macromolecules to the small intestine - Darren S. Miller; Anne Michelle Parsons; John Bresland; Paul Herde; Duc Minh Pham; Angel Tan; Hung-yao Hsu; Clive A. Prestidge; Tim Kuchel; Rezaul Begg; Syed Mahfuzul Aziz; Ross N. Butler (Journal of Zhejiang University-SCIENCE B, 2015)

Marker assisted separation of resistance genes Rph22 and Rym16 Hb from an associated yield penalty in a barley: Hordeum bulbosum introgression line - Paul A. Johnston; Vijitha Meiyalaghan; Merle E. Forbes; Antje Habekuß; Ruth C. Butler; Richard Pickering (Theoretical and Applied Genetics, 2015)

Scaffolds for Tendon and Ligament Repair and Regeneration - Anthony Ratcliffe; David L. Butler; Nathaniel A. Dyment; Paul J. Cagle; Christopher S. Proctor; Seena S. Ratcliffe; Evan L. Flatow (Annals of Biomedical Engineering, 2015)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

A temperate palaeodiversity peak in Mesozoic dinosaurs and evidence for Late Cretaceous geographical partitioning - Philip D. Mannion; Roger B. J. Benson; Paul Upchurch; Richard J. Butler; Matthew T. Carrano; Paul M. Barrett (Global Ecology and Biogeography, 2012)
Aim Modern biodiversity peaks in the tropics and declines poleward, a pattern that is potentially driven by climate. Although this latitudinal biodiversity gradient (LBG) also characterizes the marine invertebrate fossil record, distributions of ancient terrestrial faunas are poorly understood. This study utilizes data on the dinosaur fossil record to examine spatial patterns in terrestrial biodiversity throughout the Mesozoic. Location We compiled data on fossil occurrences across the globe. Methods We compiled a comprehensive dataset of Mesozoic dinosaur genera (738), including birds. Following the utilization of sampling standardization techniques to mediate for the uneven sampling of the fossil record, we constructed latitudinal patterns of biodiversity from this dataset. Results The dominant group of Mesozoic terrestrial vertebrates did not conform to the modern LBG. Instead, dinosaur diversity was highest at temperate palaeolatitudes throughout the 160 million year span of dinosaurian evolutionary history. Latitudinal diversity correlates strongly with the distribution of land area. Late Cretaceous sauropods and ornithischians exhibit disparate LBGs. Main conclusions The continuity of the palaeotemperate peak in dinosaur diversity indicates a diminished role for climate on the Mesozoic LBG; instead, dinosaur diversity may have been driven by the amount of land area among latitudinal belts. There is no evidence that the tropics acted as a cradle for dinosaur diversity. Geographical partitioning among major clades of herbivorous dinosaurs in the Late Cretaceous may result from the advanced stages of continental fragmentation and/or differing responses to increasing latitudinal climatic zonation. Our results suggest that the modern‐day LBG on land was only established 30 million years ago, following a significant post‐Eocene recalibration, potentially related to increased seasonality.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Impacts of microbial community composition on isotope fractionation during reductive dechlorination of tetrachloroethylene - Yiran Dong; Elizabeth C. Butler; R. Paul Philp; Lee R. Krumholz (Biodegradation, 2011)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Palaeoenvironmental controls on the distribution of Cretaceous herbivorous dinosaurs - Richard J. Butler; Paul M. Barrett (The Science of Nature, 2008)

Palaeoenvironmental controls on the distribution of Cretaceous herbivorous dinosaurs - Richard J. Butler; Paul M. Barrett (The Science of Nature, 2008)

Relationship between pancreatic vesicular monoamine transporter 2 (VMAT2) and insulin expression in human pancreas - Yoshifumi Saisho; Paul E. Harris; Alexandra E. Butler; Ryan Galasso; Tatyana Gurlo; Robert A. Rizza; Peter C. Butler (Journal of Molecular Histology, 2008)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)

Applications of pedigree-based genome mapping in wheat and barley breeding programs - Mandy Christopher; Emma Mace; David Jordan; David Rodgers; Paul McGowan; Ian Delacy; Phillip Banks; John Sheppard; David Butler; David Poulsen (Euphytica, 2007)

Validation of quantitative trait loci for Ascochyta blight resistance in pea (Pisum sativum L.), using populations from two crosses - Gail M. Timmerman-Vaughan; Tonya J. Frew; Ruth Butler; Sarah Murray; Margy Gilpin; Karla Falloon; Paul Johnston; Michael B. Lakeman; Adrian Russell; Tanveer Khan (Theoretical and Applied Genetics, 2004)

A multicenter case–control study of diet and lung cancer among non-smokers - Paul Brennan; Cristina Fortes; Joel Butler; Antonio Agudo; Simone Benhamou; Sarah Darby; Michael Gerken; Karl-Heinz Jöckel; Michaela Kreuzer; Sandra Mallone; Fredrik Nyberg; Hermann Pohlabeln; et al. (Cancer Causes & Control, 2000)